Property distribution of farmstead and petty nobility (szlachta) in Kuyavia at the turn of the 15th and 16th centuries = Rozmieszczenie własności szlachty zagrodowej i cząstkowej na Kujawach na przełomie XV i XVI wieku - Karczewska, Joanna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is a scientific reconnaissance on the issue of the distribution of property of the peasantless nobility and partial nobility in Kuyavia in the late Middle Ages and the early modern period. Its highest density was to be found in Przedecz Poviat (Przedecz) in Brześć Kujawski Voivodeship. The saturation of farmstead property in Kuyavia was already strong in the mid-15th century, but in the following century it began to shrink due to the concentration of noble property as accomplished by affluent nobility.
Keywords: Kuyavia; farmstead nobility; noble estate; Kujawy; szlachta zagrodowa; majątek szlachecki